Serum cystatin C to creatinine ratio is associated with sarcopenia in non-dialysis-dependent chronic kidney disease - Jung Nam An; Jwa-Kyung Kim; Hyung-Seok Lee; Sung Gyun Kim; Hyung Jik Kim; Young Rim Song (The Korean Society of Nephrology, 2022)
Background Sarcopenia is a prevalent complication in patients with chronic kidney disease and is associated with poor quality of life, morbidity, and mortality. Several candidate biomarkers have been evaluated for this condition. This study assessed the serum cystatin C to creatinine (serum cystatin C/Cr) ratio as a potential biomarker for sarcopenia in patients with non-dialysis-dependent chronic kidney disease. Methods This study enrolled 517 outpatients. Muscle mass (lean tissue index) was measured using a bioimpedance spectroscopic device, and muscle strength (handgrip strength) was also measured. Sarcopenia was defined as a combination of low muscle strength and low muscle mass. Results Sarcopenia was observed in 25.5% of patients, and the mean serum cystatin C/Cr ratio was significantly higher in patients with sarcopenia than in those without it (1.14 ± 0.26 vs. 1.01 ± 0.27, p < 0.001). The prevalence of sarcopenia and low lean tissue index increased as the cystatin C/Cr ratio increased. The negative predictive value of the cystatin C/Cr ratio for sarcopenia or low lean tissue index was ≥80%. Multivariate analyses revealed that when the serum cystatin C/Cr ratio increased by 1, the risk of sarcopenia, low lean tissue index, and low handgrip strength increased by 4.6-, 7.2-, and 2.6-fold, respectively (p = 0.003, p < 0.001, and p = 0.048). The association was maximized in patients with an estimated glomerular filtration rate of <30 mL/min/1.73 m2. Conclusion Calculating the serum cystatin C/Cr ratio could be helpful for detecting and managing sarcopenia in patients with chronic kidney disease.